Family environment as a predictor and moderator of cognitive and psychosocial outcomes in children treated for posterior fossa tumors. Issue 5 (4th July 2021) - Laliberté Durish, Christianne; Moxon-Emre, Iska; Bouffet, Eric; Bartels, Ute; Mabbott, Donald J.
ABSTRACT: Objective . The current study examined the effects of clinical factors (i.e., treatment type, history of cerebellar mutism) as well as environmental factors (i.e., family environment) as predictors of cognitive and psychosocial outcomes in children treated for posterior fossa tumors. Method . Twenty-seven children/adolescents treated for posterior fossa tumors (treatment type: radiation [ n = 12], surgery [ n = 15]; history of mutism: yes [ n = 7], no [ n = 20]) and n = 13 healthy controls, aged 8–17 years, and their caregivers completed measures assessing cognitive and psychosocial functioning, as well as the family environment (i.e., parental education, family functioning, family psychiatric history). Hierarchical linear regression analyses were conducted to examine the role of clinical factors and the family environment as predictors of cognitive and psychosocial outcomes. Family environment was also examined as a moderator of clinical factor group differences in outcomes. Results . Regression analyses revealed lower intelligence scores among the radiation group compared to the control group, lower verbal memory scores among both treatment groups compared to the control group, and a significant positive effect of parental education on verbal memory scores. Further, history of cerebellar mutism predicted poorer performance on a speeded naming task, and this relationship was moderated by family functioning, with a greater effect of mutism present among those with poorer family functioning. Conclusions . Interventions aimed at improving the family environment may help to mitigate negative cognitive effects of pediatric brain tumors, particularly among those most at-risk for poor outcomes.